The Impact of Hydration Level on Groundhandling Officer at Bandara Soekarno Hatta - Siti Zubaidah; Doni Hikmat Ramdhan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Groundhandling workers are workers who are exposed to heat for quite a long time. A work environment that exceeds tolerance limits can cause health problems such as dehydration and fatigue. Lestari (2016) in his research stated that a hot work environment that exceeds the Threshold Limit Value (TLV) can increase the risk of dehydration. Purpose: This research focuses on fatigue and the risk factors of fatigue, especially those caused by dehydration, without disregarding other risk factors among ground handling workers at Soekarno-Hatta Airport. Method: The method used in this research is an observational analytic approach with a cross-sectional design. The sampling technique employed random sampling with a sample size of 219 respondents consisting of ground handling workers working both inside buildings and on the apron. The measuring instruments used were specific gravity urine tests to determine hydration status and IFRC questionnaires to assess workers' physical fatigue status. Result: From the existing data it was found that the majority of respondenst experienced mild fatigue, namely 36,5% of the 219 respondents and others experienced severe fatigue 63,5%. With hydration status, most workers have good hydration status (euhydration), namely 70,3% and and some others experienced dehydration, namely 29,7%. The result of the analysis between hydration status and level fatigue showed 35,4% of respondents who werw dehydrated experienced severe fatigue, while 37% of respondents who were euhydrated/normohydrated experirienced severe fatgue. The results of the analysis test obtained was no relationship between hydratin status and fatigue level. The OR (Odd Ratio) shows a result or 0,932 meaning that respondents withs dehyration are protective factor of 0,93 times agains severe fatigue. Conclusion: The conclusion of this research is that good hydraton status can prevent fatigue in workers, especially those who work with direct heat exposure.